Prevalência de sobrepeso/obesidade e nível econômico de escolares - Azambuja, Ana Paula de O.; Netto-Oliveira, Edna Regina; de Oliveira, Amauri Aparecido B.; Azambuja, Maximiliano dos Anjos [UNESP]; Rinaldi, Wilson (FapUNIFESP (SciELO), 2013)
Objective: To associate the nutritional status of elementary schoolchildren with their gender, age group, and economic status based on a cross-sectional study carried out at public schools in the municipality of Cruzeiro do Oeste, Southern Brazil. Methods: The study was performed in 2010 including 939 schoolchildren aged six to ten years-old. The economical status of the families was classified based on a socioeconomic ranking questionnaire (Brazilian Association of Survey Companies), and the body mass index was calculated. Data were analyzed by descriptive statistics, and differences between independent groups were verified by Mann-Whitney and Kruskal-Wallis tests, while possible associations were verified by the chi-square test, being significant p<0.05. Results: The prevalence of obesity in the sample was 8.0%, and overweight, 16.4%. No association was found between the socioeconomic and nutritional status or between the nutritional status and gender. Conclusions: A high prevalence of overweight and obesity was found in this study, indicating that children of both genders are affected regardless of their economical status and age.
Prevalence of overweight/obesity and economical status of schoolchildren
Keywords: Children; Obesity; Overweight; body mass; Brazil; child; child health; controlled study; cross-sectional study; female; human; major clinical study; male; nutritional status; obesity; preschool child; prevalence; school child; social status